A Mixed Methods Study of Teacher Concerns Toward the Implementation of Blended Learning - Walker, Melissa Dandy (My University, 2017)
This mixed-methods study examined the behaviors and concerns of K-12 teachers in Georgia undergoing the transformational change of implementing blended learning in the classroom. A sample of 106 full-time Georgia K-12 teachers’ concerns were examined through the lens of the Concerns-Based Adoption Model (CBAM). The data was collected in two phases for this explanatory sequential mixed-methods study: Phase I (quantitative) consisted of SEDL’s online SoCQ, while two data sets, one of the open-ended questions on the SoCQ and semi-structured interviews, provided the evidence for Phase II, the qualitative phase. The results of this study indicate that teachers in Georgia are in the early concern stages regarding the implementation of blended learning. An analysis of the quantitative data indicated a significant relationship between the peak Stage of Concern and age and number of years implementing blended learning. Analysis of the qualitative data indicated teachers’ top three concerns centered around blended learning resources, school technology, and student home WIFI and technology access. This study may prove valuable in enhancing our understanding of blended learning practices in school classrooms to assist with addressing teachers’ concerns with the implementation of blended learning. While several existing studies examined the SoCQ with a focus on the integration of technology into the classroom, limited research is available through the lens of blended learning. Implications from this study could expand the scope of research on blended learning in the K-12 setting.
Chapter I INTRODUCTION 1 | Statement of the Problem 3 | Theoretical Framework 6 | Research Questions 9 | Methodology 10 | Significance of the Study 10 | Definitions of Terms 11 | Limitations 12 | Organization of the Study 13 | Chapter II REVIEW OF THE LITERATURE 14 | 21st Century Teaching and Learning 15 | Blended Learning in K-12 Schools 18 | Benefits of Blended Learning 21 | Barriers to Technology Implementation 25 | Professional Learning 27 | Professional Learning: Focus on Blended Learning 30 | Concerns Based Adoption Model (CBAM) 32 | Demographic Factors and the Stages of Concern 37 | Stages of Concern Interventions for Support 37 | Summary 38 | Chapter III METHODOLOGY 39 | Purpose of the Study 40 | Research Questions 40 | Methodology 41 | Population and Sample 42 | Selection of Participants 43 | Instrumentation 44 | Phase I: Quantitative Phase. 44 | Phase II: Qualitative Phase. 45 | Validity 47 | Reliability 48 | Data Collection 49 | Phase I: Quantitative Data Collection 50 | Phase II: Qualitative Data Collection 51 | Timeline for Data Collection 51 | Data Analysis 53 | Phase I Data Analysis 55 | Phase II Data Analysis 56 | Protection of Human Subjects 58 | Summary 58 | Chapter IV RESULTS 60 | Descriptive Statistics 62 | Presentation and Analysis of Data 63 | Phase 1: Quantitative Phase 64 | Research Question 1. 64 | Research Question 2. 73 | Phase II: Qualitative Phase 85 | Research Question 3. 85 | Summary 100 | Chapter V DISCUSSION 102 | Purpose of the Study 103 | Related Literature 104 | Methods 108 | Limitations 110 | Summary of the Findings 111 | Discussion 121 | Implications of the Results 124 | Recommendations for Future Research 126 | Summary 128 | REFERENCES 130 | APPENDIX A: Institutional Review Board Approval 161 | APPENDIX B: SEDL License Agreement 163 | APPENDIX C: Email to District Technology Leaders 166 | APPENDIX D: Email to Participants to Participate in Quantitative Phase (Survey) 168 | APPENDIX E: Questionnaire Used in the Study 170 | APPENDIX F: Email to Participants in Qualitative Phase (Interview) 177 | APPENDIX G: Email Script for Interview 179 | APPENDIX H: Interview Protocol 181 | APPENDIX I: Process of Data Analysis for Qualitative Data 184 | APPENDIX J: Themes for Research Question 3 186 | APPENDIX K: Actions to Support Change 189 | APPENDIX L: The 35 SoCQ Items Grouped by Stage 192 |
Keywords: Dissertations, Academic--United States; United States--Georgia.; Education; Blended Learning